2021
DOI: 10.1089/can.2020.0109
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol-Driven Alterations to Inflammatory Protein Landscape of Lipopolysaccharide-Activated Macrophages In Vitro May Be Mediated by Autophagy and Oxidative Stress

Abstract: Background: The nonpsychotropic phytocannabinoid cannabidiol (CBD) presents itself as a potentially safe and effective anti-inflammatory treatment relative to clinical standards. In this present study, we compare the capacity of CBD to the corticosteroid dexamethasone (Dex) in altering the secreted protein landscape of activated macrophages and speculate upon the mechanism underpinning these alterations. Materials and Methods: Human THP-1 monocytes were differentiated into macrophages (THP-1 derived macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…LPS is widely used in experiments to induce an inflammatory response, and numerous studies have shown an overproduction of IL-1β, IL-6 and TNF-6 in THP-1 cells stimulated by LPS [34][35][36]. In our study, the activation of THP-1 macrophages with LPS produced an abundant release of IL-6, IL-1β and TNF-α in the cell culture supernatants.…”
Section: Discussionsupporting
confidence: 57%
“…LPS is widely used in experiments to induce an inflammatory response, and numerous studies have shown an overproduction of IL-1β, IL-6 and TNF-6 in THP-1 cells stimulated by LPS [34][35][36]. In our study, the activation of THP-1 macrophages with LPS produced an abundant release of IL-6, IL-1β and TNF-α in the cell culture supernatants.…”
Section: Discussionsupporting
confidence: 57%
“…Another work in colorectal cancer cells also demonstrates autophagy by increasing ROS overproduction-mediated mitochondrial dysfunction due to CBD application (4 μM) [ 8 ]. In addition, in human THP-1 monocytes, a higher concentration of CBD (25 μM) can also promote the expression of cyclooxygenase 2 [ 32 ], which generates nitric oxide responsible for oxidative stress and associated pro-inflammation and pathogenic stimulation [ 33 ]. Moreover, CBD used before and after irradiation of keratinocytes with UVB showed a significant reduction in the total formation of MDA- and 4-HNE-protein adducts [ 34 ].…”
Section: Cannabidiol a Natural Compound Interfering With Redox Balancementioning
confidence: 99%
“…Data from Gonzalez-Garcia et al, (2017) indicate that CBD induces apoptosis of encephalitogenic cells through oxidative stress induction (increase in ROS) in murine MS [210]. CBD has also been shown to increase the oxygen consumption rate and enhance mitochondrial bioenergetics [190], and at high concentrations can promote COX-2 expression in LPS-treated macrophages [216]. In further support of the pro-oxidant capacity of CBD, it is also important to note that CBD has been shown to increase the expression of the NOX4 and p22phox NAP(P)H oxidases [208], and also enhances the production of the p47 subunit of pro-oxidative NADPH oxidase in endotoxin-treated neutrophils from healthy subjects [217].…”
Section: Pro-oxidant Effects Of Cbdmentioning
confidence: 99%